Aceh Education Specificity Policy: Study on Efforts to Educate Islamic Values (Memadrasahkan) Toward Public Schools in Aceh - Amirul Haq RD; Mahmud Arif; Rahmad Syah Putra (Proceeding International Conference on Religion, Science and Education, 2023)
Aceh is one of the provinces that has the authority to apply Islamic law in a kaffah manner as stipulated in the Law on the Government of Aceh (UUPA) Number 11 of 2006. The concept of implementing Islamic law in a kaffah manner includes the field of education as well which is organized based on Islamic values. Islamic values include 3 main things, namely aqidah (belief), worship and akhlak (moral). In carrying out the mandate of the law, the Aceh government formulated an Islamic education curriculum such as local content curriculum which is the authority of the Regional Government in carrying out education. The purposes of this research are: 1) to find out how the Government of Aceh implements an Islamic education curriculum as a region that has specificity, 2) to find out the efforts to educate Islamic values (memadrasahkan) toward public schools by Governor Regulation (Pergub) Number 01 of 2022 concerning Aceh Local Content Curriculum. This research was applied qualitative research method with an analytical descriptive approach. Furthermore, it was used data collection techniques with documentation and interview techniques, while data analysis was carried out gradually, namely: data reduction, data presentation, and conclusions verification/drawing. The Aceh government with its authority formulated a local content curriculum in the form of a Governor Regulation (Pergub). The local content curriculum includes the contents of the subjects: a) Aqidah Akhlak subject; b) Al-Qur’an and Hadist subject; c) Fiqh subject; d) Islamic Cultural History subject; e) Arabic subject; and f) other local content subjects. All of these subjects are similar as taught in the curriculum of Madrasah, in practice, however, there are differences in the time allocation per week based on the Decree of the Minister of Religion (KMA) number 184 of 2019 concerning Curriculum Implementation in Madrasah.